Perancangan dan Implementasi Sistem Point of Sale (POS) yang Terintegrasi dengan Inventory Gudang Menggunakan Metode Waterfall - Eka Yulianti; Laila Kaltsum Hafizhah Salma; Faiz Farid Afifi; Toti Fernanda Suprapto (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Conventional Point of Sale (PoS) systems that are not integrated with warehouse management systems often cause inventory management issues, such as discrepancies between stock levels and sales data. This can lead to operational losses due to inaccurate decision-making. This research aims to design and implement a PoS system directly connected to an online inventory management system to address these issues. The waterfall model was used in developing this system, consisting of several stages: needs analysis, system design, implementation, testing, and maintenance. Each stage was implemented sequentially to ensure the system ran according to required specifications. The results of this research indicate that the developed PoS system successfully improved operational efficiency by streamlining the sales transaction documentation process and accelerating the verification of inventory availability in the warehouse. Furthermore, the system is equipped with automatic sales reporting and stock update features, reducing the potential for human error in data recording. With the integration of the PoS system and warehouse management, companies can manage transactions and inventory more effectively, in real time, and in an organized manner. The overall system developed can be a relevant and applicable technology solution for retailers and medium-sized businesses to improve their operational accuracy and productivity.